Electrochemical Behaviours and Electrocatalytic Properties of the PW12O403- (Collagen-PW12O403-)n /Cysteamine Modified Gold Electrode - Liu, L.; Song, Y.H.; Chen, C.Y.; Zhang, M.; Yuan, H.Z.; Wang, L. (Asian Journal of Chemistry, 2011)
A novel multilayer of the type I collagen and PW12O403- was successfully constructed on cysteamine modified gold electrode. Electrochemistry and atomic force microscopy (AFM) were used to characterize the PW12O403- (collagen-PW12O403-)n multilayer modified gold electrode. Atomic force microscopy images showed that the PW12O403- preferentially deposited on the collagen network to produce the three-dimensional PW12O403- network. Electrochemical results indicated that the modified electrode exhibited good electrochemical behaviours and electrocatalytic activity towards the reduction of NO2–. The electrochemical behaviours and electrocatalytic properties of the modified electrode were investigated in detail.